Perbedaan Efektivitas Metode Demonstrasi dan Pemutaran Video Animasi Dalam Meningkatkan Pengetahuan Cuci Tangan Pakai Sabun Siswa SDN 043/XI Koto Renah - Sri Handayani; Zafira Nurul Fiza; Ilma Nuria Surleni (Poltekkes Kemenkes Padang, 2022)
Hand washing is one of the most important interventions which is effective in preventing the infection of various microbial diseases. Based on Riskesdas data (2018) the level of knowledge of CTPS in Indonesian society is still low, only 17% of school-age children are performing the correct CTPS. One of the ways to increase knowledge of CTPS is through health promotion. The purpose of this study was to determine the differences in the effectiveness of the demonstration method and animated video playback in increasing knowledge about CTPS among grade IV students of SDN 043/XI Koto Renah. This type of research uses a quasi-experimental approach with a two-group pre-post test design approach. The research population was all IV grade students of SDN 043/XI Koto Renah. The sampling technique used is total sampling. The study was conducted from June 3 to 4 June, 2021. Data were analyzed univariately in the form of frequency distribution and bivariate using dependent t-test statistical test and independent t-test. The results showed that there was no significant difference between the demonstration method and the animation video playback method. The statistical test results obtained a p-value of 0.229 > 0.005, meaning that the demonstration method and animated video playback were equally effective in increasing students' knowledge of CTPS.